2006
DOI: 10.1097/01.ccm.0000241155.36689.91
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of short-term consequences of hypoglycemia in an intensive care unit*

Abstract: In this study, no association between incidental hypoglycemia and mortality was found. However, this data set is too small to definitely exclude the possibility that hypoglycemia is associated with intensive care unit mortality. In three patients with possible hypoglycemia-associated coma or seizures, a causal role for hypoglycemia seemed likely but could not fully be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
0
3

Year Published

2007
2007
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(107 citation statements)
references
References 15 publications
1
103
0
3
Order By: Relevance
“…When correcting for patient risk factors and duration of exposure to insulin (ICU stay), studies found that hypoglycemia could still be associated with increased mortality risk (Leuven MICU study: OR 2.4 [P<0.001]) or it would disappear as an independent factor for mortality (Leuven SICU study: OR 1.9 [P=0.17]; and Leuven PICU study: OR 2.1 [P= 0.32]). Nested-case control studies, also correcting for on-admission risk factors and duration of ICU stay, could not demonstrate a causal link between hypoglycemia and mortality or increased serum levels of brain injury markers [42,43]. The latter study provided evidence that brain injury markers were already raised before the hypoglycemic event occurred, illustrating that baseline severity of illness is the chief contributor to the risk of hypoglycemia and elevated brain injury markers.…”
Section: Risk Of Hypoglycemiamentioning
confidence: 92%
“…When correcting for patient risk factors and duration of exposure to insulin (ICU stay), studies found that hypoglycemia could still be associated with increased mortality risk (Leuven MICU study: OR 2.4 [P<0.001]) or it would disappear as an independent factor for mortality (Leuven SICU study: OR 1.9 [P=0.17]; and Leuven PICU study: OR 2.1 [P= 0.32]). Nested-case control studies, also correcting for on-admission risk factors and duration of ICU stay, could not demonstrate a causal link between hypoglycemia and mortality or increased serum levels of brain injury markers [42,43]. The latter study provided evidence that brain injury markers were already raised before the hypoglycemic event occurred, illustrating that baseline severity of illness is the chief contributor to the risk of hypoglycemia and elevated brain injury markers.…”
Section: Risk Of Hypoglycemiamentioning
confidence: 92%
“…Regarding the consequences of non-life-threatening hypoglycemia, long-term cognitive and other neurologic impairments were sometimes reported, but not in critically ill patients experiencing short-term hypoglycemic episodes [ 33 ]. These fi ndings do not necessarily imply that patients with longer-lasting hypoglycemia are not at risk.…”
Section: Risks and Hazards Of Hypoglycemiamentioning
confidence: 95%
“…B. Bakteriämien, Nierenversagen und Poly neuropathien [27]. Die gefürchtete uner wünschte Nebenwirkung der IIT, die häu fig dem Umsetzen des Konzeptes in die Praxis entgegensteht, ist die Hypoglykä mie, obwohl es bei Intensivpatienten bis her keinen definitiven Nachweis gibt, dass eine kurzzeitige Hypoglykämie unter IIT eine attribuierbare neuropsychologische Dysfunktion oder Letalität verursacht [14,18,20,27,31].…”
Section: Hintergrundunclassified